IMPROVING STUDENT’S SPEAKING SKILL BY USING COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD AT TENTH GRADE OF SMA NEGERI 1 LAHUSA - Laia, Rani Hati (Universitas Nias Raya, 2024)
Language is tool for human to share feeling and idea and when we building communication with other we need speaking where in Speaking is a activities that can do all human to interact for other people or transfer information by language, Speaking is one of the components in teaching English and make a connection between one person to another got information or share the idea and massage. This research aimed to Improving student’s Speaking Skill by using Communicative Language Teaching (CLT) Method at Tenth Grade of SMA Negeri 1 Lahusa. The researcher used theory Richards and Rodgers, to Improving student’s speaking because this method can devoted students to communication in english by carrying out actual social interactions, such as presentation and discussion. To find out the result of research used data analysis, the result is analyzed by assessing speaking they are accent, grammar, vocabulary, fluency and comprehension from CAR (classroom action research ) (quantitative data) and data collection take from observation and documentation (qualitative data). The implementation communicative language teaching method involving students in the learning process. Communicative Language Teaching method is appropriate in teaching speaking skill. In teaching apply by researcher to solve the students problem in speaking ability. Communicative language teaching method in the learning teaching process can make the students active, involved and free and confidence-self when we try make interest in without puss down their motivate in the learning process.